The influence relationship of creative thinking on the quality of work life, an analytical study on people’s officials in the General Directorate of Education of Baghdad Governorate, Rusafa / second - Dawood, Ahmed Quinn; Shaalan, Uday Hussien; Nsaif, Ahmed Kamil (Technium Social Sciences Journal, 2022)
The research aims to test the relationship of influence and correlation of creative thinking , As the independent variable with his skills that have been adopted, Represented by (frameworks of creative thinking, causation, and synthesis )In the quality of work life in its sub-dimensions (compensation, share, supervision, work environment, opportunities for growth and development (as a dependent variable,By adopting the descriptive analytical method , The research sample includes officials of the people of the General Directorate of Education in Baghdad, Rusafa II , They numbered (93) individuals , who represent the research community, By adopting the questionnaire as the main tool for data collection, distributed to all sample members , and retrieve (74) valid for statistical analysis, A number of appropriate statistical methods were used in the research , Which represented (arithmetic mean, standard deviation, correlation, regression, Facronbach's coefficient and split-half) , And the most prominent conclusions that were reached were embodied in the existence of a statistically significant relationship between the independent variable (creative thinking) with its dimensions with the dependent variable (quality of work life) with its dimensions, In the research sample, there is a significant significant effect of the independent variable (creative thinking) with its dimensions, on the dependent variable (quality of work life) with its dimensions, The research sample also showed the ability to show creative thinking skills , And that they have the ability to adopt change and put forward innovative ideas that increase the strength of the organization and achieve its goals.